2002
DOI: 10.1017/s0950268801006562
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination against hepatitis B in low endemic countries

Abstract: A mathematical model that takes transmission by sexual contact and vertical transmission into account was employed to describe the transmission dynamics of hepatitis B virus (HBV) and vaccination against it. The model is an extension of a model by Williams et al. (Epidemiol Infect 1996: 116; 71-89) in that it takes immigration of hepatitis B carriers from countries with higher prevalence into account. Model parameters were estimated from data from The Netherlands where available. The main results were that, gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
28
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 8 publications
6
28
0
1
Order By: Relevance
“…The nurses, however, were well trained for this type of survey. Kretzschmar et al [2002] acknowledges the problem of self-reported data on sexual behavior, and refers to a large survey conducted in The Netherlands on sexual behavior that includes 1,001 respondents [Zessen and Sandfort, 1991]. These studies suggest that surveys taken by experienced nurses are optimal ways of obtaining data on sexual behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nurses, however, were well trained for this type of survey. Kretzschmar et al [2002] acknowledges the problem of self-reported data on sexual behavior, and refers to a large survey conducted in The Netherlands on sexual behavior that includes 1,001 respondents [Zessen and Sandfort, 1991]. These studies suggest that surveys taken by experienced nurses are optimal ways of obtaining data on sexual behavior.…”
Section: Discussionmentioning
confidence: 99%
“…In a large part of the general population, the virus cannot maintain itself without the import of new cases from the outside [Kretzschmar et al, 2002]. Import is observed, primarily through contacts (e.g., intermarriage) with the migrant population.…”
Section: Discussionmentioning
confidence: 99%
“…In the Netherlands this was found to be not costeffective due to the very low HBV-carrier prevalence and the relative high percentage of imported HBV-infections [5,6]. Introduction was therefore postponed until 2011 [7].…”
Section: Introductionmentioning
confidence: 99%
“…The reproductive number for HBV infection was estimated at 0.69-1.11 in the low endemic areas of the Netherlands and UK (Kretzschmar et al 2002). In these areas, the HBV transmission route was environmental with horizontal transmission, and the spread of HBV infection was therefore lower in their countries than our study because vertical transmission was rampant in Taiwan, particularly in southern area.…”
Section: Discussionmentioning
confidence: 53%